2010
DOI: 10.1007/s12272-010-0702-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-nociceptive activities of compounds from Tinospora sagittata (Oliv.) Gagnep.

Abstract: Radix Tinosporae is a herb widely used in traditional Chinese medicine for the treatment of various inflammatory diseases. In the present study, its anti-inflammatory and antinociceptive activities were investigated. The ethanol extract of Radix Tinosporae exhibited significant inhibitory effects on xylene-induced ear edema and acetic acid-induced writhing in mice. Using bioassay-guided fractionation, the n-butanol fraction was determined as the active fraction. Further purification of the most active n-butano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The clear ROESY correlations (l " Fig. 3) for H-10/H-19, H-19/H-8 and H-8/H-12 indicated that H-10, H-19, and H-8 were on the same side of the molecular plane, and tentatively assuming an α-orientation according to the previously isolated diterpenoids from the Tinospora genus [2][3][4][16][17][18][19][20][21][22][23][24][25][26]. Finally, the structure of compound 1 was elucidated as shown in l " Fig.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The clear ROESY correlations (l " Fig. 3) for H-10/H-19, H-19/H-8 and H-8/H-12 indicated that H-10, H-19, and H-8 were on the same side of the molecular plane, and tentatively assuming an α-orientation according to the previously isolated diterpenoids from the Tinospora genus [2][3][4][16][17][18][19][20][21][22][23][24][25][26]. Finally, the structure of compound 1 was elucidated as shown in l " Fig.…”
mentioning
confidence: 67%
“…Its roots have widely been used for the treatment of sore throats, diarrhea, and superficial infections [1]. Previous investigations on the genus Tinospora showed that the clerodane diterpenes possess anti-inflammatory, antibacterial, and antifeedant activity [2][3][4][5][6]. In our recent study on the bioactivity of the Tinospora plants, the 95 % ethanolic extract of T. sagittata var.…”
mentioning
confidence: 99%
“…A voucher specimen (TSG2014) was deposited in the Veterinary Medicine Department of Sichuan Agricultural University. We prepared an extract of TSG from the plants according to reported methods [21]. Air-dried TSG (500 g) was refluxed with 95 % ethanol ( v/v ) three times each for 2 h. The solvent was completely removed in vacuo to generate a semisolid residue, which yielded 14.72 % ( w/w ) dry starting material.…”
Section: Methodsmentioning
confidence: 99%
“…R. tinosporae is widely distributed in south of China, that is, Hunan, Guangdong, Guangxi, Guizhou, Sichuan, and Hubei provinces . In contemporary pharmacological study, it has been demonstrated that R. tinosporae has many biological activities, such as anti‐inflammatory , antibiosis, and antiviral effects . According to the literature, the major bioactive components in R. tinosporae can be divided into three types, including alkaloids, terpenoids, and sterols .…”
Section: Introductionmentioning
confidence: 99%